STRATEGI PARTAI NASIONAL DEMOKRAT DALAM MENGHADAPI PILKADA SERENTAK TAHUN 2015 PROVINSI SUMATERA UTARA - Malau, Roslinda Wati; Hasibuan, Muhammad Aswin; Nasution, Irwan (Universitas Medan Area, 2020)
Research conductedby researchers titled ?Strategi Partai Nasional Demokrat (NasDem) Dalam Menghadapi Pilkada Serentak Tahun 2015 (Studi Pada Dewan Perwakilan Wilayah Partai Nasional Demokrat Provinsi Sumatera Utara?. The purpose of this study aims to know a strategy of the party Nasional Demokrat (NasDem) in the face of the election simultaneously. A strategy of political is a set of the approach overall related to the implementation of the idea of, planning to a political party can win a fight between a variety of thepower of political process of reform happened where the political process be coming more berdinamika and demokrasi colored by a fight between the very open, until finally neededthe existance of a strategy of political using different approaches in which included noticed a political issue that will be sold to the group voters, take account of the power of her own, and observe the ability of the party of the competitors being political rival. Then in the study this will be seen now the Nasional Demokrat (NasDem) do a variety of things strategy in eforts won a political as the location of the study aut hors. How strong a strategy of political party Nasional Demokrat (NasDem) as the party of the bow of nationalist with all the instruments are there in which answered a political happened, to be able to win pilkada serentak that took place on 9 December 2015 and immediately able to be the preferred and take root in a society. In the study aut hors this will use analysis SWOT, as the theoretically to meausure the extent strength, weakness, the odds, and the threat of faced by the party Nasional Demokrat (NasDem). Including how the Nasional Demokrat (NasDem) tackle obstacles faced during the process of a sound in the effort to win pilkada serentak years 2015.